Sie sind auf Seite 1von 26

# 香港青年協會 會考寬頻 27771112.

hk

AL
P MATHS
Paper I

2010
Beacon College

This paper must be answered in English

3 hours
By Oscar Tam

## 1. This paper consists of Section A and Section B.

2. Answer ALL questions in Section A, using the AL(C) answer book.
3. Answer any FOUR questions in Section B, using the AL(E) answer book.
4. Unless otherwise specified, all working must be clearly shown.

## Not to be taken away before the

end of the examination session

1
Reference material, not for sale

## sin ( A ± B ) = sin A cos B ± cos A sin B

cos( A ± B ) = cos A cos B μ sin A sin B
tan A ± tan B
tan ( A ± B ) =
1 μ tan A tan B
A+ B A− B
sin A + sin B = 2 sin cos
2 2
A+ B A− B
sin A − sin B = 2 cos sin
2 2
A+ B A− B
cos A + cos B = 2 cos cos
2 2
A+ B A− B
cos A − cos B = −2 sin sin
2 2
2 sin A cos B = sin( A + B ) + sin( A − B )
2 cos A cos B = cos( A + B ) + cos( A − B )
2 sin A sin B = cos( A − B ) − cos( A + B )

2
Reference material, not for sale

## SECTION A (40 marks)

Answer ALL questions in this section.

## (1) A sequence {u1 , u 2 ,Λ } of real numbers is defined by u1 = 1 , u 2 = 2 and u n = 2u n −1 + u n − 2

for all n = 3, 4, Λ .

## Show that for all positive integers n, u n =

1
( )
α n − β n , where α, β are the roots of
2 2
x − 2 x − 1 = 0 with α > β .
2

Given that v n =
1
( )
α n + β n for all n = 1, 2, Λ .
2 2
Are vn positive integers for all n ∈ N ?
(6 marks)

2x − 3 1
(2) (a) Solve the inequality < , where x is a real number.
x + 11 3
21 − 3 y − 3 1
(b) Using the result of (a), or otherwise, solve the inequality < , where y is
1 − 3 y + 11 3
a real number.
(5 marks)

(3) For any positive integer n, let C kn be the coefficient of x k in the expansion of (1 + x ) .
n

## (a) Show that C1n + 2 2 C 2n x + 3 2 C 3n x 2 + Λ + n 2 C nn x n −1 = n(1 + x ) + n(n − 1)x(1 + x )

n −1 n−2
.

(b) (i)
C 2 C 3
Show that C 0n x + x + 1
n n
x +Λ +
2 C n
x n +1 =
n (1 + x ) − 1 . n +1

2 3 n +1 n +1

30 2
r Cr 30 2
( )
= 30C 29
59
.
r =1 31 − r
(9 marks)

## (4) A 2×2 matrix M represents a transformation T which maps (1, 1) and (− 1, 1) to 0, 2 2 ( )

( )
and 2 2 , 0 respectively.
(a) Find M.
⎛ a b ⎞⎛ λ 0 ⎞ a b
(b) Decompose M as ⎜⎜ ⎟⎟⎜⎜ ⎟⎟ where λ > 0 and = −1 .
⎝ c d ⎠⎝ 0 λ ⎠ c d
Hence describe the geometric meaning of the transformation T.
( )
(c) If T transforms the point (α, β) to − 4 2 , 2 2 , find the values of α and β.
(8 marks)

3
Reference material, not for sale

## (5) Let f (x ) = 5 x 3 − 21x 2 + (k + 20 )x − 12 and g ( x ) = 10 x 3 − 12 x 2 + (2k − 21)x + 6 , where k

is a non-negative integer.
Let α be a common root of the equations f ( x ) = 0 and g ( x ) = 0 .
(a) Find the value(s) of α.
(b) Hence, find all the roots of f ( x ) = 0 .
(6 marks)

## (6) A sequence of real numbers {a n } is defined as follows:

a1 = 5 and a n +1 = 5 + a n , n = 1, 2, 3, Λ .
(a) Show that {a n } is bounded above by 3.
(b) Show that {a n } is convergent and find the limit.
(6 marks)

4
Reference material, not for sale

## SECTION B (60 marks)

Answer any FOUR questions in this section. Each question carries 15 marks.

## (7) Consider the system of linear equations in x, y, z:

⎧ ax + y + z = p
(E ) : ⎪⎨ x + ay + z = q , where a, p, q, r ∈ R .
⎪ax + y + az = r

(a) Find the range of values of a for which (E) has a unique solution. Solve (E) when (E)
has a unique solution.
(6 marks)
(b) For each of the following cases, find the condition(s) on p, q and r for which (E) is
consistent.
(i) a = 1 ,
(ii) a = −1.
(3 marks)
⎧ x − y − z = 3

(c) If there are more than one solutions (x, y, z ) of (F ) : ⎨− x + y − z = −1 satisfy
⎪ x − y + z =1

x 2 − ( py − 1) + z 2 = 1 , find the range of values of p.
2

(6 marks)

## (8) Let M be the set of all 3× 3 real matrices.

For any A, B ∈ M , A is said to be similar to B if and only if there is an invertible matrix
P ∈ M such that A = PBP −1 .
(a) For any A, B, C ∈ M , show that
(i) if A is similar to the zero matrix, then A is the zero matrix,
(ii) A is similar to A,
(iii) if A is similar to B, then B is similar to A,
(iv) if A is similar to B, then A n is similar to B n for all positive integers n,
(v) if A is similar to B and B is similar to C, then A is similar to C.
(5 marks)
(b) Find two matrices A and B in M such that AB and BA are not similar.
(4 marks)
(c) Let A ∈ M and λ1 , λ 2 , λ 3 ∈ R .
⎛ λ1 0 0⎞ ⎛ x1 ⎞
⎜ ⎟ ⎜ ⎟
Show that A is similar to ⎜ 0 λ2 0 ⎟ if and only if there exist matrices ⎜ y1 ⎟ ,
⎜0 λ 3 ⎟⎠ ⎜z ⎟
⎝ 0 ⎝ 1⎠
⎛ x2 ⎞ ⎛ x3 ⎞ ⎛ x1 x2 x3 ⎞ ⎛ xi ⎞ ⎛ xi ⎞
⎜ ⎟ ⎜ ⎟ ⎜ ⎟ ⎜ ⎟ ⎜ ⎟
⎜ y 2 ⎟ and ⎜ y 3 ⎟ where ⎜ y1 y2 y3 ⎟ are invertible and A⎜ y i ⎟ = λ i ⎜ y i ⎟ for
⎜z ⎟ ⎜z ⎟ ⎜z z 3 ⎟⎠ ⎜z ⎟ ⎜z ⎟
⎝ 2⎠ ⎝ 3⎠ ⎝ 1 z2 ⎝ i⎠ ⎝ i⎠
i = 1, 2, 3.
(6 marks)

5
Reference material, not for sale

(9) (a) Let α, β, γ be the roots of the equation x 3 + 3ax 2 + 3bx + c = 0 . Show that

α + β + γ = −3a
αβ + βγ + γα = 3b
αβγ = −c
(3 marks)
(b) Show that the roots of x + 3ax + 3bx + c = 0 form an arithmetic sequence if and
3 2

only if 2a 3 − 3ab + c = 0 .
(5 marks)
(c) Let α, β and γ be the roots of the equation x + 4 x + 2 x + k = 0 , where k is a
3 2

## constant. Find the values of k such that α 2 , β 2 , γ 2 form an arithmetic sequence.

(5 marks)
(d) For the greater value of k found in (b), find all the roots of x + 4 x + 2 x + k = 0 .
3 2

(2 marks)

## (10) (a) Show that for any x ≥ 0 , f ( x ) =

x
is increasing.
1+ x
(2 marks)
(b) For any non-negative real numbers x1 , x 2 ,Λ , x n , show that
x1 + x 2 + Λ + x n x x2 xn
≤ 1 + +Λ + .
1 + x1 + x 2 + Λ + x n 1 + x1 1 + x 2 1 + xn
Under what condition will the equality hold?
(5 marks)
(c) For any non-negative real numbers x1 , x 2 ,Λ , x n , show that
n

∑x
n

x1 x 2 Λ x n r n n
xr
≤ r =1
≤∑ .
1 + x1 x 2 Λ x n n
n + xr
n
n + ∑ xr r =1
n

r =1
(4 marks)
(d) Hence, show that for all positive real numbers x1 , x 2 ,Λ , x n ,
n ⎛ xr n 1 ⎞⎟
∑ ⎜

r =1 ⎝ n + x r
n
+
nx r + 1 ⎟⎠
n
≥ 1.

(4 marks)

π
(11) (a) For any positive integer n and 0 < θ < , using De Moivre’s theorem, or otherwise,
2
show that
cot 7 θ − 21cot 5 θ + 35 cot 3 θ − 7 cot θ
cot 7θ = .
7 cot 6 θ − 35 cot 4 θ + 21cot 2 θ − 1
(4 marks)

6
Reference material, not for sale

## (b) By considering the equation cot 7θ = 1 , or otherwise, find the value of

6
(4k + 1)π .
∑k =0
cot 2
28
Hence, find
6
(i) ∑ csc 2
(4k + 1)π ,
k =0 28
6
(ii) ∑ sec 2
(13 − 4k )π ,
k =0 28
(11 marks)

End of paper

7
Reference material, not for sale

## Marking Scheme Marks

(1) When n = 1 ,

L.H.S. = u1
= 1,

R.H.S. =
1
(α − β)
2 2
=
1
(α − β)2
2 2
=
1
(α + β)2 − 4αβ 1A
2 2
2 2 − 4(− 1)
1
=
2 2
1
= 8
2 2
= 1.

When n = 2 ,

L.H.S. = u 2
= 2,

R.H.S. =
1
(α 2
− β2 )
2 2
=
1
(α + β)(α − β)
2 2
=
1
(2)( 8 )
2 2
= 2.

## Assume the statement is true when n = k and n = k + 1 , i.e.,

uk =
1
(α k
− β k ) and u k +1 =
1
(α k +1
− β k +1 ).
2 2 2 2

8
Reference material, not for sale

## Consider the statement when n = k + 2 ,

u k + 2 = 2u k +1 + u k

= 2⋅
1
(α k +1 − β k +1 ) + 1 (α k − β k )
2 2 2 2
=
1
[ (2α k +1 + α k ) − (2β k +1 + β k ) ]
2 2
=
1
[ α k (2α + 1) − β k (2β + 1) ] 1M
2 2
=
1
[ ]
α k (α 2 ) − β k (β 2 ) 1M
2 2
=
1
(α k +2 − β k +2 ).
2 2

Consider

v1 =
1
(α + β)
2 2
1
= ⋅2
2 2
1
= , 1A
2

## ∴ vn are not positive integers for all n ∈ N . 1A

2x − 3 1
(2) (a) <
x + 11 3
(2 x − 3)2 <
1
1M
(x + 11)2 9
(x + 11)2 > 9(2 x − 3)
2

## [3(2 x − 3) − (x + 11)][3(2 x − 3) + (x + 11)] <0 1M

5( x − 4)(7 x + 2) <0
2
− < x < 4. 1A
7

9
Reference material, not for sale

## (b) Using (a),

2
− < 1− 3 y <4 1M
7
2
− < 1 − 3y and 1 − 3y < 4
7
(All real values of y) and − 4 < 1 − 3y < 4
5
−1 < y < .
3

5
∴ −1 < y < . 1A
3

## (3) (a) (1 + x )n = C 0n + C1n x + C 2n x 2 + C 3n x 3 + Λ + C nn x n

n(1 + x )
n −1
= C1n + 2C 2n x + 3C 3n x 2 + Λ + nC nn x n −1 1M
nx (1 + x ) = C1n x + 2C 2n x 2 + 3C 3n x 3 + Λ + nC nn x n
n −1

## n(1 + x ) + n(n − 1)x(1 + x )

n −1 n−2
= C1n + 2 2 C 2n x + 3 2 C 3n x 2 + Λ + n 2 C nn x n −1 . 1

## (b) (i) Consider

∫ (1 + x )
n
( )
dx = ∫ C 0n + C1n x + C 2n x 2 + C 3n x 3 + Λ + C nn x n dx 1M
(1 + x )n+1 + C = C 0n x +
C1n 2 C 2n 3
x +
Cn
x + Λ + n x n +1 .
n +1 2 3 n +1

## Put x = 0 into the above expression,

1
+C =0
n +1
1
C =− .
n +1

Hence,

C1n 2 C 2n 3 C nn n +1 (1 + x )n +1 − 1
C x+
n
x + x +Λ + x = . 1
n +1 n +1
0
2 3

29 28
(1) 1A

## and using (b),

10
Reference material, not for sale

C130 2 C 230 3
C 030 x +
x +
C 30
x + Λ + 30 x 31 =
(1 + x )31 − 1
2 3 31 31
30
C 29 2 C 2 29 C1 30 C 0 31 (1 + x )31 − 1
30 30 30
C30 x +
30
x +Λ + x + x + x = . (2) 1M
2 29 30 31 31

Hence, ∑
r 2 C r30
30
( ) 2

is the coefficient of x 30 in
r =1 31 − r

⎡ (1 + x )31 − 1⎤
[30(1 + x ) 29
+ 870 x(1 + x )
28
]
⎢ ⎥. 1A
⎣ 31 ⎦

Thus,

30
( )
r 2 C r30
2

r =1 31 − r

## 30(1 + x ) + 870 x(1 + x ) − 30(1 + x ) − 870 x(1 + x )

60 59 29 28
= Coefficient of x 30 in 1
31
30 60 870 59
= C 30 + C 29
31 31
30 60! 870 59
= ⋅ + C 29
31 30!⋅ 30! 31
30 60 59! 870 59
= ⋅ ⋅ + C 29
31 30 29!⋅ 30! 31
60 59 870 59
= C 29 + C 29
31 31
= 30C 29
59
. 1

⎛ w x⎞
(4) (a) Let M = ⎜⎜ ⎟⎟ , then
⎝ y z⎠

⎛ w x ⎞ ⎛1⎞ ⎛ 0 ⎞ ⎛ w x ⎞ ⎛ − 1⎞ ⎛ 2 2 ⎞
⎜⎜ ⎟⎟ ⎜⎜ ⎟⎟ = ⎜⎜ ⎟⎟ and ⎜⎜ ⎟⎟ ⎜⎜ ⎟⎟ = ⎜⎜ ⎟

⎝ y z ⎠⎝ ⎠ ⎝
1 2 2 ⎠ ⎝ y z ⎠⎝ ⎠ ⎝1 0 ⎠
⎛ w + x⎞ ⎛ 0 ⎞ ⎛− w + x⎞ ⎛2 2 ⎞
⎜⎜ ⎟⎟ = ⎜⎜ ⎟⎟ and ⎜⎜ ⎟⎟ = ⎜⎜ ⎟.

⎝ y + z ⎠ ⎝ 2 2 ⎠ ⎝ − y + z ⎠ ⎝ 0 ⎠

⎧ w+ x = 0

⎪− w + x = 2 2
∴⎨ . 1A
⎪ y+z =2 2
⎪− y + z = 0

11
Reference material, not for sale

## On solving the above system, we have w = − 2 , x = 2 ,

y = 2 , z = 2.

⎛− 2 2⎞
∴ M = ⎜⎜ ⎟. 1A
⎝ 2 2 ⎟⎠

⎛− 2 2 ⎞ ⎛a b ⎞⎛ λ 0 ⎞
(b) ⎜ ⎟ = ⎜⎜ ⎟⎜ ⎟
⎜ 2
⎝ 2 ⎟⎠ ⎝ c d ⎟⎠⎜⎝ 0 λ ⎟⎠
⎛ aλ bλ ⎞
= ⎜⎜ ⎟.
⎝ cλ dλ ⎟⎠

⎧ aλ = − 2

⎪ bλ = 2
∴⎨ . 1A
⎪ cλ = 2

⎩ dλ = 2

As

a b
= −1
c d
⎛ 2⎞⎛ 2⎞ ⎛ 2⎞⎛ 2⎞
⎜− ⎟⎜ ⎟ ⎜ ⎟⎜ ⎟
⎜ λ ⎟ ⎜ λ ⎟ −⎜ λ ⎟⎠ ⎜⎝ λ ⎟⎠
= −1 1M
⎝ ⎠⎝ ⎠ ⎝
λ2 =4
λ = 2. (Θ λ > 0)

2 2
∴ a=− , b=c=d = . 1A
2 2

Thus,

⎛ 2 2 ⎞⎟
⎜−
M =⎜ 2 2 ⎟⎛⎜ 2 0 ⎞⎟ .
⎜ 2 2 ⎟⎜⎝ 0 2 ⎟⎠
⎜ ⎟
⎝ 2 2 ⎠

## Geometric meaning: T transforms a point by enlarging by a 1A + 1A

scale factor of 2 and then reflect in the
⎛ 3π ⎞
line y = ⎜ tan ⎟ x .
⎝ 8 ⎠

12
Reference material, not for sale

(c) Consider

T
1 ⎛ 2 − 2⎞
M −1
= ⎜ ⎟
det M ⎜− 2 − 2 ⎟⎠

1 ⎛ 2 − 2⎞
= ⎜ ⎟
− 4 ⎜⎝ − 2 − 2 ⎟⎠
⎛ 2 2⎞
⎜− ⎟
=⎜ 4 4 ⎟.
⎜ 2 2⎟
⎜ ⎟
⎝ 4 4 ⎠

Since

⎛α⎞ ⎛− 4 2 ⎞
M ⎜⎜ ⎟⎟ = ⎜⎜ ⎟,

β
⎝ ⎠ ⎝ 2 2 ⎠

⎛ 2 2⎞
⎜ ⎟
⎛α⎞ ⎜− 4 4 ⎟ ⎛⎜ − 4 2 ⎞⎟
⎜⎜ ⎟⎟ =
⎝β⎠ ⎜ 2 2 ⎟ ⎜⎝ 2 2 ⎟⎠
⎜ ⎟
⎝ 4 4 ⎠
⎛3⎞
= ⎜⎜ ⎟⎟ .
⎝ − 1⎠

∴ α = 3 and β = −1 . 1A

⎧⎪ 5α 3 − 21α 2 + (k + 20 )α − 12 = 0 (1)
(5) (a) ⎨ .
⎪⎩10α 3 − 12α 2 + (2k − 21)α + 6 = 0 (2 )

(2) − (1) × 2 : 1M

30α 2 − 61α + 30 = 0
6 5
α= or α = . 1A for both correct
5 6

5
Put α = into (1), 1M
6

3 2
⎛5⎞ ⎛5⎞ ⎛5⎞
5⎜ ⎟ − 21⎜ ⎟ + (k + 20 )⎜ ⎟ − 12 = 0
⎝6⎠ ⎝6⎠ ⎝6⎠
1517
k = ,
180

13
Reference material, not for sale

## which is not a non-negative integer.

6
Put α = into (1), 1M
5

3 2
⎛6⎞ ⎛6⎞ ⎛6⎞
5⎜ ⎟ − 21⎜ ⎟ + (k + 20 )⎜ ⎟ − 12 = 0
⎝5⎠ ⎝5⎠ ⎝5⎠
k = 8.

6
∴ α= . 1A
5

## (b) Using (a),

f (x ) = 0
5 x − 21x + 28 x − 12 = 0
3 2

## (5x − 6)(x − 1)(x − 2) = 0

6
x = , 1, 2. 1A for all correct
5

a k +1 = 5 + a k
≤ 5+3 1M
< 3.

When n = 1 ,

a 2 = 5 + a1
= 5+ 5
> 5
= a1 .

## Therefore, the statement is true when n = 1 .

14
Reference material, not for sale

## Consider the statement when n = k + 1 ,

5 + a k +1 ≥ 5 + a k
5 + a k +1 ≥ 5 + a k 1M
a k + 2 ≥ a k +1 .

## Let lim a n = l , then

n→∞

lim a n +1 = lim 5 + a n
n→∞ n →∞

l = 5+l
l −l −5 = 0
2
1A
1 + 21 1 − 21
l= or l = . (rejected)
2 2

1 + 21
Thus, lim a n = . 1A
n →∞ 2

a 1 1
(7) (a) Δ = 1 a 1
a 1 a
= a3 − a2 − a + 1
= (a − 1) (a + 1) .
2
1A

## Thus, (E) has a unique solution if and only if

Δ≠0 ≠ 0 1A
⇔ (a − 1) (a + 1) ≠ 0
2

⇔ a ≠ 1 and a ≠ −1 . 1A

## Using the Cramer’s rule,

15
Reference material, not for sale

p 1 1
q a 1
r 1 a
x =
Δ
=
(a − 1)[ p(a + 1) − q − r ]
(a − 1)2 (a + 1)
p(a + 1) − q − r
= , 1A
(a − 1)(a + 1)
a p 1
1 q 1
a r a
y =
Δ
=
(a − 1)(aq − r )
(a − 1)2 (a + 1)
aq − r
= 1A
(a − 1)(a + 1)
and

a 1 p
1 a q
a 1 r
z =
Δ
=
(
(r − p ) a 2 − 1 )
(a − 1) (a + 1)
2

r−p
= . 1A
a −1

⎧x + y + z = p

(b) (i) When a = 1 , (E) becomes ⎨ x + y + z = q .
⎪x + y + z = r

## Thus, (E) is consistent when p = q = r . 1A

⎧− x + y + z = p

(ii) When a = −1, (E) becomes ⎨ x − y + z = q .
⎪− x + y − z = r

## Using the Gaussian elimination,

16
Reference material, not for sale

⎛−1 1 1 p⎞ ⎛ 1 −1 1 q ⎞
⎜ ⎟ R1 ↔ R2
⎜ ⎟
⎜ 1 −1 1 q ⎟ ⎜−1 1 1 p⎟ 1M
⎜−1 1 −1 r ⎟ ⎜ −1 1 −1 r ⎟
⎝ ⎠ ⎝ ⎠
⎛1 −1 1 q ⎞
R1 + R2
⎜ ⎟
⎜0 0 2 p + q⎟ .
R1 + R3 ⎜0 0 0 q + r ⎟
⎝ ⎠

## Thus, (E) is consistent when q + r = 0 . 1A

⎧− x + y + z = −3

(c) Rewrite (F) as ⎨ x − y + z = 1 .
⎪− x + y − z = −1

## When a = −1 , p = −3 , q = 1 and r = −1 , the system (E) becomes

(F). Using (b) (ii), the system (F) has infinitely many solutions. 1A

⎧x − y + z = 1
Using the Gaussian elimination, (F) becomes ⎨ .
⎩ 2 z = −2

2
1M + 1A
have

## (t + 2)2 − ( pt − 1)2 + (− 1)2 =1

(1 − p 2 )t 2 + (4 + 2 p )t + 3 = 0. (*) 1A

Thus,

## 1 − p 2 ≠ 0 and (4 + 2 p ) − 4(1 − p 2 )(3) > 0

2
1A
p ≠ ±1 and (2 p + 1) > 0 .
2

## ∴ The range of values of p is all real numbers except − 1 , 1

1
and − . 1A
2

(8) (a) (i) If A is similar to the zero matrix, then there exists an
invertible matrix P ∈ M such that

A = P 0 P −1
= 0.

17
Reference material, not for sale

## (ii) For any A ∈ M ,

A = IAI −1 .

Thus, A is similar to A. 1

## (iii) If A is similar to B, then there exists an invertible matrix P

such that A = PBP −1 .

Thus,

B = P −1 AP
= P −1 A(P −1 ) .
−1

## (iv) If A is similar to B, then there exists an invertible matrix P

such that A = PBP −1 .

Hence,

(
A n = 1PBP −1
)(
PBP −1 Λ PBP −1
4 4 4 42 4 4 4 43
) ( )
n times
−1
= PB P . n

Thus, A n is similar to B n . 1

## (v) If A is similar to B and B is similar to C, then there exist

invertible matrices P and Q such that A = PBP −1 and
B = QCQ −1 .

Thus,

(
A = P QCQ −1 P −1 )
= (PQ )C (PQ ) .
−1

## As P and Q are invertible, PQ is also invertible.

Hence A is similar to C. 1

⎛1 0 0⎞ ⎛0 0 1⎞
⎜ ⎟ ⎜ ⎟
(b) Consider A = ⎜ 0 0 0 ⎟ and B = ⎜ 0 0 0 ⎟ . 1A
⎜0 0 0⎟ ⎜ 0 0 0⎟
⎝ ⎠ ⎝ ⎠

18
Reference material, not for sale

Then

⎛1 0 0⎞ ⎛0 0 1⎞
⎜ ⎟⎜ ⎟
AB = ⎜ 0 0 0 ⎟ ⎜ 0 0 0 ⎟
⎜ 0 0 0⎟ ⎜ 0 0 0⎟
⎝ ⎠⎝ ⎠
⎛0 0 1⎞
⎜ ⎟
= ⎜ 0 0 0⎟ 1A
⎜ 0 0 0⎟
⎝ ⎠

and

⎛ 0 0 1⎞ ⎛1 0 0⎞
⎜ ⎟⎜ ⎟
BA = ⎜ 0 0 0 ⎟ ⎜ 0 0 0 ⎟
⎜ 0 0 0⎟ ⎜0 0 0⎟
⎝ ⎠⎝ ⎠
⎛ 0 0 0⎞
⎜ ⎟
= ⎜ 0 0 0⎟ . 1A
⎜ 0 0 0⎟
⎝ ⎠

## Using (a) (i), if AB is similar to BA, then AB is a zero matrix. 1

As AB is not a zero matrix, AB and BA are not similar.

## (c) Only if part

⎛ λ1 0 0⎞
⎜ ⎟
If A is similar to ⎜ 0 λ2 0 ⎟ , then there exists an invertible
⎜0
⎝ 0 λ 3 ⎟⎠
matrix P such that

⎛ λ1 0 0⎞
⎜ ⎟
A = P⎜ 0 λ2 0 ⎟ P −1 1M
⎜0
⎝ 0 λ 3 ⎟⎠
⎛ λ1 0 0⎞
⎜ ⎟
AP = P⎜ 0 λ2 0 ⎟.
⎜0
⎝ 0 λ 3 ⎟⎠

## ⎛ x1 x2 x3 ⎞ ⎛ a11 a12 a13 ⎞

⎜ ⎟ ⎜ ⎟
Let P = ⎜ y1 y2 y 3 ⎟ and A = ⎜ a 21 a 22 a 23 ⎟ , then
⎜z
⎝ 1 z2 z 3 ⎟⎠ ⎜a
⎝ 31 a32 a33 ⎟⎠

19
Reference material, not for sale

## ⎛ a11 a12 a13 ⎞ ⎛ x1 x2 x3 ⎞ ⎛ x1 x2 x3 ⎞ ⎛ λ 1 0 0⎞

⎜ ⎟⎜ ⎟ ⎜ ⎟⎜ ⎟
⎜ a 21 a 22 a 23 ⎟ ⎜ y1 y2 y3 ⎟ = ⎜ y1 y2 y3 ⎟ ⎜ 0 λ2 0⎟
⎜a a33 ⎟⎠ ⎜⎝ z1 z 3 ⎟⎠ ⎜⎝ z1 z 3 ⎟⎠ ⎜⎝ 0 λ 3 ⎟⎠
⎝ 31 a32 z2 z2 0

## ⎛ a11 x1 + a12 y1 + a13 z1 a11 x 2 + a12 y 2 + a13 z 2 a11 x3 + a12 y 3 + a13 z 3 ⎞

⎜ ⎟
⎜ a 21 x1 + a 22 y1 + a 23 z1 a 21 x 2 + a 22 y 2 + a 23 z 2 a 21 x3 + a 22 y3 + a 23 z 3 ⎟
⎜a x + a y + a z
⎝ 31 1 32 1 33 1 a31 x 2 + a32 y 2 + a33 z 2 a31 x3 + a32 y3 + a33 z 3 ⎟⎠
⎛ λ1 x1 λ 2 x2 λ 3 x3 ⎞
⎜ ⎟
= ⎜ λ 1 y1 λ 2 y2 λ 3 y3 ⎟ .
⎜λ z
⎝ 1 1 λ 2 z2 λ 3 z 3 ⎟⎠

⎛ xi ⎞ ⎛ xi ⎞
⎜ ⎟ ⎜ ⎟
Hence, A⎜ y i ⎟ = λ i ⎜ y i ⎟ for i = 1, 2, 3. 1
⎜z ⎟ ⎜z ⎟
⎝ i⎠ ⎝ i⎠

If part

⎛ x1 x2 x3 ⎞
⎜ ⎟
Let P = ⎜ y1 y2 y 3 ⎟ . Clearly, P is invertible. 1M
⎜z
⎝ 1 z2 z 3 ⎟⎠

Consider

⎛ x1 x2 x3 ⎞
⎜ ⎟
AP = A⎜ y1 y2 y3 ⎟
⎜z
⎝ 1 z2 z 3 ⎟⎠
⎛ λ1 x1 λ 2 x2 λ 3 x3 ⎞
⎜ ⎟
= ⎜ λ 1 y1 λ 2 y2 λ 3 y3 ⎟
⎜λ z
⎝ 1 1 λ 2 z2 λ 3 z 3 ⎟⎠
⎛ x1 x2 x3 ⎞ ⎛ λ 1 0 0 ⎞
⎜ ⎟⎜ ⎟
= ⎜ y1 y2 y3 ⎟ ⎜ 0 λ2 0 ⎟. 1A
⎜z
⎝ 1 z2 z 3 ⎟⎠ ⎜⎝ 0 0 λ 3 ⎟⎠

Thus,

⎛ λ1 0 0⎞
⎜ ⎟
A = P⎜ 0 λ2 0 ⎟ P −1 . 1A
⎜0
⎝ 0 λ 3 ⎟⎠

20
Reference material, not for sale

⎛ λ1 0 0⎞
⎜ ⎟
Hence, A is similar to ⎜ 0 λ2 0 ⎟. 1
⎜0 λ 3 ⎟⎠
⎝ 0

## (9) (a) x 3 + 3ax 2 + 3bx + c = ( x − α )( x − β)( x − γ ) 1M

= x 3 − (α + β + γ )x 2 + (αβ + βγ + γα )x − αβγ .

## Thus, by comparing coefficients on both sides,

⎧3a = −(α + β + γ )

⎨3b = αβ + βγ + γα . 1A
⎪ c = −αβγ

⎧ α + β + γ = −3a

Thus, ⎨αβ + βγ + γα = 3b . 1
⎪ αβγ = −c

## The roots form an arithmetic sequence

⇔ α + γ = 2β or β + α = 2 γ or β + γ = 2α 1M
⇔ (α + γ − 2β) (α + β − 2γ ) (β + γ − 2α ) = 0 1M
⇔ [(α + β + γ ) − 3β] [(α + β + γ ) − 3γ ] [(α + β + γ ) − 3α] = 0 1M
⇔ (− 3a − 3β) (− 3a − 3γ ) (− 3a − 3α ) = 0
⇔ (a + α ) (a + β) (a + γ ) = 0 1A
⇔ a + (α + β + γ ) a + (αβ + βγ + γα )a + αβγ = 0
3 2

⇔ a 3 − 3a ⋅ a 2 + 3b ⋅ a − c = 0
⇔ 2a 3 − 3ab + c = 0 . 1

(c) Let y = x 2 . 1M

x3 + 4x 2 + 2x + k = 0
( ) (
x x 2 + 2 = − 4x 2 + k ) 1M
x 2 (x 2 + 2 ) = (4 x 2 + k )
2 2

y ( y + 2 ) = (4 y + k )
2 2

y 3 − 12 y 2 + (4 − 8k ) y − k 2 = 0 . (*) 1A

## Using (b), if α 2 , β 2 , γ 2 form an arithmetic sequence,

21
Reference material, not for sale

⎛ 4 − 8k ⎞
2(− 4 ) − 3(− 4 )⎜ ⎟−k = 0
3 2
1M
⎝ 3 ⎠
k 2 + 32 k + 112 = 0
k = −4 or k = −28 . 1A

## (d) When k = −4 , the equation becomes

x3 + 4x 2 + 2x − 4 = 0 .

Note that

## (− 2)3 + 4(− 2)2 + 2(− 2) − 4 = 0 .

Hence,

x3 + 4x 2 + 2x − 4 = 0
(
(x + 2) x 2 + 2 x − 2 ) = 0 1M
x = −2 or x = −1 ± 3 . 1A

f ′( x ) =
(1 + x ) − x 1M
(1 + x )2
1
=
(1 + x )2
> 0. 1A

## As f ( x ) is continuous at x = 0 , f ( x ) is increasing for x ≥ 0 .

(b) Consider

x1 + x 2 + Λ + x n
1 + x1 + x 2 + Λ + x n
x1 x2 xn
= + +Λ +
1 + x1 + x 2 + Λ + x n 1 + x1 + x 2 + Λ + x n 1 + x1 + x 2 + Λ + x n
x x xn
≤ 1 + 2 +Λ + 1M
1 + x1 1 + x 2 1 + xn

as x1 , x 2 ,Λ , x n are non-negative.

## Equality holds if and only if for 1 ≤ j ≤ n ,

22
Reference material, not for sale

xj xj
= 1M
1 + x1 + x 2 + Λ + x n 1+ x j
x j (1 + x j ) = x j (1 + x1 + x 2 + Λ + x n )
x j (x1 + Λ + x j −1 + x j +1 + Λ + x n ) = 0 . 1A

## If x j ≠ 0 , then xi = 0 for i = 1, 2, Λ , n and i ≠ j . Hence, equality

holds if and only if x1 , x 2 ,Λ , x n are all zero or exactly one of 1A + 1A
them is non-zero.

## (c) Using A.M. ≥ G.M., we have 1M

x1 + x 2 + Λ + x n
n n n

≥ n x1 x 2 Λ x n
n n n

n
= x1 x 2 Λ x n .

Thus,

x1 + x 2 + Λ + x n
n n n

x1 x 2 Λ x n n
≤ (using (a)) 1M
1 + x1 x 2 Λ xn x1 + x 2 + Λ + x n
n n n

1+
n
n

∑x
n
r
= r =1
n
.
n + ∑ xr
n

r =1

Also,
n n n n

∑x x1 x x
n
r + 2 +Λ + n
r =1
n
= n n n n n
n
n + ∑ xr x x x
n
1+ 1 + 2 +Λ + n
r =1 n n n
n n n
x1 x2 xn
≤ n n + n n +Λ + n
n
(using (b)) 1M
x1 x2 xn
1+ 1+ 1+
n n n
n n n
x1 x2 xn
= + + Λ +
n + x1 n + x2 n + xn
n n n

n n
xr
=∑ . 1
n + xr
n
r =1

23
Reference material, not for sale

1
(d) As x1 , x 2 ,Λ , x n are all positive, by replacing xr by in 1M
xr

x1 x 2 Λ x n n n
x
≤∑ r n (1)
1 + x1 x 2 Λ xn r =1 n + x r

we have

n
⎛ 1 ⎞⎛ 1 ⎞ ⎛ 1 ⎞ ⎛1⎞
⎜⎜ ⎟⎟⎜⎜ ⎟⎟ Λ ⎜⎜ ⎟⎟ ⎜⎜ ⎟⎟
⎝ x1 ⎠⎝ x 2 ⎠ ⎝ x n ⎠ ≤ ⎝ xr ⎠
n

⎛ 1 ⎞⎛ 1 ⎞ ⎛ 1 ⎞
∑ n

1 + ⎜⎜ ⎟⎟⎜⎜ ⎟⎟ Λ ⎜⎜ ⎟⎟
r =1 ⎛1 ⎞
n + ⎜⎜ ⎟⎟
⎝ x1 ⎠⎝ x 2 ⎠ ⎝ x n ⎠ ⎝ xr ⎠
n
1 1
≤∑ . (2) 1A
x1 x 2 Λ x n + 1 r =1 nx r + 1
n

(1) + (2) : 1M

n n n
xr 1
1 ≤∑ +∑
n + xr nx r + 1
n n
r =1 r =1

n ⎛ xr n 1 ⎞⎟
∑ ⎜

r =1 ⎝ n + x r
n
+
nx r + 1 ⎟⎠
n
≥ 1. 1

Also,

## (cos θ + i sin θ)7

= cos 7 θ + 7 cos 6 θ ⋅ (i sin θ) + 21 cos 5 θ ⋅ (i sin θ ) + 35 cos 4 θ ⋅ (i sin θ ) +
2 3

## 35 cos 3 θ ⋅ (i sin θ ) + 21 cos 2 θ ⋅ (i sin θ ) + 7 cos θ ⋅ (i sin θ ) + (i sin θ )

4 5 6 7
1A
= (cos 7 θ − 21cos 5 θ sin 2 θ + 35 cos 3 θ sin 4 θ − 7 cos θ sin 6 θ) +
i (7 cos 6 θ sin θ − 35 cos 4 θ sin 3 θ + 21 cos 2 θ sin 5 θ − sin 7 θ) .

## ⎧⎪cos 7θ = cos 7 θ − 21 cos 5 θ sin 2 θ + 35 cos 3 θ sin 4 θ − 7 cos θ sin 6 θ

∴⎨ . 1M
⎪⎩ sin 7θ = 7 cos 6 θ sin θ − 35 cos 4 θ sin 3 θ + 21 cos 2 θ sin 5 θ − sin 7 θ

Hence,

24
Reference material, not for sale

cot 7θ
cos 7 θ − 21 cos 5 θ sin 2 θ + 35 cos 3 θ sin 4 θ − 7 cos θ sin 6 θ
=
7 cos 6 θ sin θ − 35 cos 4 θ sin 3 θ + 21cos 2 θ sin 5 θ − sin 7 θ
cos 7 θ − 21 cos 5 θ sin 2 θ + 35 cos 3 θ sin 4 θ − 7 cos θ sin 6 θ
= sin 7 θ 1M
7 cos θ sin θ − 35 cos θ sin 3 θ + 21 cos 2 θ sin 5 θ − sin 7 θ
6 4

sin 7 θ
cot θ − 21cot θ + 35 cot 3 θ − 7 cot θ
7 5
= . 1
7 cot 6 θ − 35 cot 4 θ + 21 cot 2 θ − 1

## (b) (i) Consider

cot 7θ = 1
π
7θ = nπ +
4
θ =
(4n + 1)π
, n∈Z. 1A
28

Thus, cot
(4n + 1)π are the roots of the equation 1M
28

x 7 − 21x 5 + 35 x 3 − 7 x
=1
7 x 6 − 35 x 4 + 21x 2 − 1
x 7 − 7 x 6 − 21x 5 + 35 x 4 + 35 x 3 − 21x 2 − 7 x + 1 = 0 . (*)

π 5π 9π 13π 17 π
Note that cot , cot , cot , cot , cot , 1M
28 28 28 28 28
21π 25π
cot and cot are all distinct and are the roots of (*). 1A
28 28

Thus,

6
(4k + 1)π = 7 2 − 2(− 21)
∑ cot
k =0
2

28
1M + 1A

= 91 . 1A

6
(4k + 1)π 6
⎡ (4k + 1)π + 1⎤
(i) ∑ csc 2
k =0 28
= ∑ ⎢cot 2
k =0 ⎣ 28 ⎥⎦ 1M
6
= ∑ cot 2
(4k + 1)π + 7
k =0 28
= 91+ 7
= 98 . 1A

25
Reference material, not for sale

6
(13 − 4k )π 6
⎡ π (13 − 4k )π ⎤
(ii) ∑ sec
k =0
2

28
= ∑ csc 2 ⎢ −
k =0 ⎣2 28 ⎥

1M
6
= ∑ csc 2
(4k + 1)π
k =0 28
= 98 . 1A

26
Reference material, not for sale